(untitled) (Research, Society and Development, 2020)
Pressure injury can be determined as an injury that arises on the skin or tissues of parts of the body that have bony prominence. This lesion can be superficial or deep, in order to present tissue necrosis. The study aimed to analyze the perception of nurses about nursing care in the treatment and prevention of pressure injuries in patients admitted to Clinical-Surgical Units of a hospital located in the region of Vale do Taquari, in Rio Grande do Sul (RS). This research is characterized as a qualitative, exploratory and descriptive study, carried out with nurses who work in the Clinical-Surgical Units of a hospital located in the Vale do Taquari region, in RS. The collected data were studied using the theme analysis technique, proposed by Minayo, and covered three stages: pre-analysis, exploration of the material and treatment of the results. The results point to the following categories: treatment of pressure injuries in inpatient units, guidelines performed by nurses, importance of a Commission for the Treatment of Wounds and specific protocols and prevention of pressure injuries in inpatient units. The research can contribute to sensitize the nursing team that works at the hospital of the hospital under study, promoting a reflection on their way of care, so that, from that, they can implement improvements in the care of patients with pressure injuries or in prevention complications or primary prevention, aiming to improve the quality of care for inpatients.